2017
DOI: 10.14715/cmb/2017.63.12.14
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and phenotypic characterization of the vancomycin-resistant gene in bacterial isolates acquired from catheter tips

Abstract: Gram-positive bacteria, particularly Staphylococcus aureus is a significant pathogen, not only in the hospital setting but the community also. S. aureus is a major cause of serious hospital and community-acquired infections, particularly in the colonized individuals. The emergence of vancomycin-resistant S. aureus (VRSA) strains has led to global concerns about treatments for staphylococcal infections. Until now, few strains of VRSA have been reported worldwide. The conventional disk diffusion method for deter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…HAIs increase mortality, length of hospital stay, cost of care, bacterial resistance, antibiotic use, etc in intensive care units (ICUs), particularly in developing countries. 1,2 The International Nosocomial Infection Control Consortium showed that the incidence rate for central line-associated bloodstream infection (CLABSI) in ICUs in developing countries was 3-fold higher than in the United States of America. 3 The implementation of a prevention CLABSI bundle can significantly reduce the occurrence of HAIs.…”
Section: Introductionmentioning
confidence: 99%
“…HAIs increase mortality, length of hospital stay, cost of care, bacterial resistance, antibiotic use, etc in intensive care units (ICUs), particularly in developing countries. 1,2 The International Nosocomial Infection Control Consortium showed that the incidence rate for central line-associated bloodstream infection (CLABSI) in ICUs in developing countries was 3-fold higher than in the United States of America. 3 The implementation of a prevention CLABSI bundle can significantly reduce the occurrence of HAIs.…”
Section: Introductionmentioning
confidence: 99%